(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
India comprises 135.26 crore people. According to National Sample Survey Organization (NSSO) IN 2009-10, the total employment in the country was of 46.5 crore comprising around 2.8 crore in organized sector and the remaining 43.7 crore workers in the unorganized sector. This unorganized sector faces many problems and challenges in regulation with employer, over time, exploitation, casual work culture and many more. The unorganized labour is engaged in casual, seasonal and scattered employment which are not unionized and because of their scattered employment nature, they do not take advantage of any labour law. It is not that there are no labour laws for the security and welfare of unorganized sector. These laws made for both organized and unorganized labours, but the conditions for the applicability of the labour laws are like that cannot be fulfilled by the unorganized sector. Unorganized workers are deprived from the social security benefits such as- Pensions, Gratuity, Workmen’s compensation, Employee State Insurance, deprived from the benefits of the acts of regarding of Regulation of Employment such as- The Factories Act, 1948, The Industrial Disputes Act, 1947, The Contract Workman Act, 1970, The Maternity Benefits Acts, 1961 and they are also deprived from the benefits of laws which give them regularity of wages such as- The Payment of Wages Act, 1936 and The Minimum Wages act, 1948. The fundamental principle of labour legislation is to guarantee the weaker party in the labour market protection and basic rights in order to be in a fair position when negotiating salary and working conditions. But when it comes to unorganized sector, this fundamental principle of labour legislation also becomes a bit tarnished. However, the Indian government is constantly making efforts for the welfare and protection of unorganized labours and in these efforts an important law is ‘Social Security Act, 2008’ to achieve its objectives, there is there is a provision for the constitution of the Board at the State level and also the funding of State Government Schemes for record keeping by district administration and for the setup of the workers facilitation centre. Unorganized sector plays a crucial role in Indian economy. For the effective implementation of labour legislation for the unorganized sectors, it is essential to the study the existing employment relations, after analyzing the existing working conditions of unorganized labours in India should be given special attention. This paper will discuss about the problems and challenges faced by unorganized labours and their conditions in the comparison of organized labours. In this paper labour laws are discussed, which benefits only the organized sector can take. Finally, some discussion has been made about some special legislations which also implement to the unorganized sector.